The genus Cladosporium - Bensch, K. (CBS Fungal Biodiversity Centre, 2012)
A monographic revision of the hyphomycete genus Cladosporium s. lat. (Cladosporiaceae, Capnodiales) is presented. It includes a detailed historic overview of Cladosporium and allied genera, with notes on their phylogeny, systematics and ecology. True species of Cladosporium s. str. (anamorphs of Davidiella), are characterised by having coronate conidiogenous loci and conidial hila, i.e., with a convex central dome surrounded by a raised periclinal rim. Recognised species are treated and illustrated with line drawings and photomicrographs (light as well as scanning electron microscopy). Species known from culture are described in vivo as well as in vitro on standardised media and under controlled conditions. Details on host range/substrates and the geographic distribution are given based on published accounts, and a re-examination of numerous herbarium specimens. Various keys are provided to support the identification of Cladosporium species in vivo and in vitro. Morphological datasets are supplemented by DNA barcodes (nuclear ribosomal RNA gene operon, including the internal transcribed spacer regions ITS1 and ITS2, the 5.8S nrDNA, as well as partial actin and translation elongation factor 1-α gene sequences) diagnostic for individual species. In total 993 names assigned to Cladosporium s. lat., including Heterosporium (854 in Cladosporium and 139 in Heterosporium), are treated, of which 169 are recognized in Cladosporium s. str. The other taxa are doubtful, insufficiently known or have been excluded from Cladosporium in its current circumscription and re-allocated to other genera by the authors of this monograph or previous authors.